Evolution of Antibiotic Resistance in Surrogates of Francisella tularensis (LVS and Francisella novicida): Effects on Biofilm Formation and Fitness - Biot, Fabrice V.; Bachert, Beth A.; Mlynek, Kevin D.; Toothman, Ronald G.; Koroleva, Galina I.; Lovett, Sean P.; Klimko, Christopher P.; Palacios, Gustavo F.; Cote, Christopher K.; Ladner, Jason T.; Bozue, Joel A. (Frontiers in Microbiology, 2020)
Francisella tularensis, the causative agent of tularemia, is capable of causing disease in a multitude of mammals and remains a formidable human pathogen due to a high morbidity, low infectious dose, lack of a FDA approved vaccine, and ease of aerosolization. For these reasons, there is concern over the use of F. tularensis as a biological weapon, and, therefore, it has been classified as a Tier 1 select agent. Fluoroquinolones and aminoglycosides often serve as the first line of defense for treatment of tularemia. However, high levels of resistance to these antibiotics has been observed in gram-negative bacteria in recent years, and resistant Francisella strains have been described in the literature. The acquisition of antibiotic resistance, either natural or engineered, presents a challenge for the development of medical countermeasures. In this study, we generated a surrogate panel of antibiotic resistant F. novicida and LVS (Live Vaccine Strain) and characterized their growth, biofilm capacity, and fitness. These experiments were carried out in an effort to 1) assess the fitness of resistant strains; and 2) identify new targets for the development of vaccines or therapeutics. All strains exhibited a high level of resistance to either ciprofloxacin or streptomycin, a fluoroquinolone and aminoglycoside, respectively. Whole genome sequencing of this panel revealed both on-pathway and off-pathway mutations, with more mutations arising in LVS. For F. novicida, we observed significantly decreased biofilm formation for all ciprofloxacin resistant strains compared to wild-type, while streptomycin resistant isolates were unaffected in biofilm capacity. The fitness of representative antibiotic resistant strains was assessed in vitro in murine macrophage-like cell lines, and also in vivo in a murine model of pneumonic infection. These experiments revealed that nearly all ciprofloxacin resistant Francisella strains tested were completely attenuated while mild attenuation was observed in streptomycin resistant strains. This study is one of the few to examine the link between acquired antibiotic resistance and fitness in Francisella spp., as well as enable the discovery of new targets for medical countermeasure development.